Association among Blink Rate, Changes in Ocular Surface Temperature, Tear Film Stability, and Functional Visual Acuity in Patients after Cataract Surgery - Takashi Itokawa; Yukinobu Okajima; Takashi Suzuki; Tatsuhiko Kobayashi; Yuto Tei; Koji Kakisu; Yuichi Hori (Journal of Ophthalmology)
Purpose. To investigate the association among the ocular surface temperature (OST), tear film stability, functional visual acuity (FVA), and blink rate in patients after cataract surgery. Methods. We recruited 98 eyes of 69 patients (mean age, 73.7 ± 5.2 years) 1 month after phacoemulsification with implantation of acrylic intraocular lenses and assessed slit-lamp microscopy, corrected distance VA, FVA, noninvasive tear breakup time (NIBUT), and OST. We defined the changes in the OST from 0 to 10 seconds after eye opening as the ΔOST. We measured the FVA and blink rate using the FVA measurement system. We divided the patients into two groups based on tear film stability: stable tear film (NIBUT, >5.0 seconds) and unstable tear film (NIBUT, ≤5.0 seconds). We evaluated the differences between the two groups and the association between the blink rate and other clinical parameters. Results. The unstable tear film group (56 eyes) had significantly (p<0.0001, unpaired t-test) shorter NIBUTs than the stable tear film group (42 eyes). The ΔOSTs and blink rates were significantly (p<0.0001) higher in the unstable tear film group than in the stable group. Linear single regression analysis showed that the ΔOST (r = −0.430, p<0.0001), NIBUT (r = −0.392, p<0.0001), and gender (r = −0.370, p=0.0002) were correlated significantly with the blink rate. Multiple regression analysis showed that the ΔOST independently contributed to the blink rate. Conclusions. The frequency of blinks is associated with tear film stability in patients after cataract surgery. The blink rate may be useful for evaluating the tear film stability in clinical practice. The ΔOST should be an important contributing factor to the blink rate. [This trial is registered with UMIN000026970].